KARAKTERISTIK BAHASA GAUL TERHADAP EKSISTENSI BAHASA INDONESIA PADA MAHASISWA USN KOLAKA - Kadirun; Aulia Ramadani (PT. CASA CENDEKIA MEDIA, 2024)
This research was conducted because it is important for us to address the use of slang language that is currently widespread among the Indonesian population, especially the students of Universitas Sembilanbelas November Kolaka. This research employs a qualitative research design. The data collection technique involves observing the phenomena of everyday conversations, both in direct interactions and through social media. The results obtained regarding the impact of slang language usage on the existence of the Indonesian language among the students of Universitas Sembilanbelas November Kolaka indicate several influencing factors, one of which is the social environment. The most significant factor is the use of social media. Certainly, the use of slang language has both positive and negative impacts when not used appropriately in different situations.